Transanal total mesorectal excision: how are we doing so far?. (26th March 2019) - Sparreboom, C. L.; Komen, N.; Rizopoulos, D.; van Westreenen, H. L.; Doornebosch, P. G.; Dekker, J. W. T.; Menon, A. G.; Tuynman, J. B.; Daams, F.; Lips, D.; van Grevenstein, W. M. U.; Karsten, T. M.; et al.
Abstract: Aim: This subgroup analysis of a prospective multicentre cohort study aims to compare postoperative morbidity between transanal total mesorectal excision (TaTME) and laparoscopic total mesorectal excision (LaTME). Method: The study was designed as a subgroup analysis of a prospective multicentre cohort study. Patients undergoing TaTME or LaTME for rectal cancer were selected. All patients were followed up until the first visit to the outpatient clinic after hospital discharge. Postoperative complications were classified according to the Clavien–Dindo classification and the comprehensive complication index (CCI). Propensity score matching was performed. Results: In total, 220 patients were selected from the overall prospective multicentre cohort study. After propensity score matching, 48 patients from each group were compared. The median tumour height for TaTME was 10.0 cm (6.0–10.8) and for LaTME was 9.5 cm (7.0–12.0) ( P  = 0.459). The duration of surgery and anaesthesia were both significantly longer for TaTME (221 vs 180 min, P  < 0.001, and 264 vs 217 min, P  < 0.001). TaTME was not converted to laparotomy whilst surgery in five patients undergoing LaTME was converted to laparotomy (0.0% vs 10.4%, P  = 0.056). No statistically significant differences were observed for Clavien–Dindo classification, CCI, readmissions, reoperations and mortality. Conclusion: The study showed that TaTME is a safe and feasible approach for rectal cancer resection. This new technique obtained similar postoperative morbidity to LaTME.